Geostrategiczne aspekty „problemu kaliningradzkiego” Geostrategic aspects of the „Kaliningrad problem” - Sakson, Andrzej (Przegląd Strategiczny, 2011)
After the collapse of the USSR, the Kaliningrad Oblast, which currently constitutes a part of the Russian Federation, has become an exclave neighboring Poland and Lithuania. After these two countries joined the European Union in 2004 the Kaliningrad Oblast has become an ‘isle in the EU’. One of the outcomes of this situation involves regular statements issued by politicians from Moscow and Kaliningrad reassuring that on account of its geostrategy the region is a permanent part of Russia. A special name has even been coined to address this matter – the Kaliningrad issue. There are two main geopolitical concepts: the region is Russia’s westernmost military outpost; and a pilot region for collaboration with the European Union. Although, different concepts have emerged concerning the increased independence and autonomy of this region, its inclusion in Russia is beyond doubt.